Implications of Migrationon Income and Welfare of Nationals - Ueda, Kenichi (IMF Working Papers; Working Paper ;, 2002)
As labor has become more mobile in today's world, it is important to understand the income and welfare of nationals regardless of their residence. This paper develops two key concepts, gross migration-corrected product (GMP) and welfare cost of migration, and calculates them using New Zealand data. Growth performance measured by New Zealanders' income has been clearly better than suggested by the GDP. The welfare cost associated with a marginal change in the tax rate appears quite high.